The Impact of Total Quality Management Implementation on Small and Medium Manufacturing Companies - Sari, Ratna Purwita; Firdaus, Achmad (Faculty of Economic and Business, 2018)
This study aims to analyze the influence of Total Quality Management (TQM) implementation to competitive advantage and company’s performance, especially to small and medium manufacturing company. Using Partial Least Square (PLS) tested the hypothesis of Structural Equation Modelling (SEM). There is significant influence between TQM implementation to competitive advantage. Likewise with a competitive advantage to the company's performance there is significant influence. But there is no significant influence directly between TQM to the company's performance. The study discusses about the implementation of TQM in small and medium manufacturing companies. In the practice, implementation of TQM in small and medium manufacturing companies are not as smooth as the large manufacturing company.DOI: 10.15408/ess.v8i1.5852